PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PENDIDIKAN ANAK DI DESA CUPANG GADING KECAMATAN SEKADAU HULI KABUPATEN SEKADAU - Marta Helina Mia; F. Y. Khosmas; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis thesis entitled, "The Influence of Parents' Social Economic Status on Children's Education in Cupang Gading Village, Sekadau Hulu District, Sekadau District", this study aims to determine the socioeconomic status of parents influencing children's education in Cupang Gading Village. The population in this study were the parents of children in the village of Cupang Gading, as many as 56 parents of children and samples taken 36 parents of children. The variables in this study consisted of 2 variables, namely the Social Economic Status of Parents (X) and Children's Education (Y). Data collection was carried out directly using questionnaires and documents. The validation of the instrument used expert judgment and reliability with internal consistency using the Alpha Cronbach technique. Based on the data analysis the researchers conducted, it was concluded that: 1) The socioeconomic status of the parents obtained the results with the most categories, namely 27, the percentage (75%) had moderate criteria. 2) Children education got the most results in the category of 30, the percentage (83%) had moderate criteria. 3) Based on Simple Linear Regression Analysis, the influence of parents' socioeconomic status on children's education is obtained by the equation 15,124 + 0.444 X means the constant value is 15,124. The regression coefficient value of the parent's socioeconomic status variable is positive, namely 36.3. The size of the influence of parents' socioeconomic status on children's education based on the results of the determination test was 36.3%, while the remaining 34.4% which is influenced by other factors and not discussed in this study.Keywords: The Influence Of Parent, Social Economic Status, On Child Education